Student's Conservation Attitudes and Behavior After Conservation and Environment-Courses - Rarasandy, Lianita; Prasetyo, Andreas Priyono Budi; Ngabekti, Sri (Universitas Negeri Semarang, 2020)
Implementation of Conservation and Environmental Education (PKLH) courses is expected to foster mental attitudes and conservation behaviors of Univeritas Negeri Semarang (UNNES) students. This is in line with the application of UNNES as a conservation university that aims to support the protection, preservation and utilization of the environment as stated in the seven pillars of conservation. Although this course has been implemented since 2010, this does not have an effect on student attitudes, as does student participation in disposing of waste according to rules that are still limited. The survey was conducted on 385 respondents to analyze the attitudes and conservation behaviors of students who have taken PKLH courses, as well as analyze the relationship between attitudes and student conservation behaviors. Data was taken using a psychological scale of attitudes and behaviors. Attitudes are measured based on cognitive, affective and conative aspects, while behavior is measured based on the seven pillars of UNNES conservation. Results showed that the conservation attitude of students who had taken PKLH courses was included in the high category, while the conservation behavior of students showed a moderate category. Correlation test shows that there is a positive and significant relationship between attitude and behavior.